Particulate matter as a possible reservoir of multidrug-resistant microorganisms in surgical healthcare settings - E. A. Chezganova; O. S. Efimova; V. M. Sakharova; A. R. Efimova; S. A. Sozinov; Z. R. Ismagilov; E. B. Brusina (Фундаментальная и клиническая медицина, 2020)
Aim. To study the microbial diversity and dust organic component in surgical healthcare settings and to assess the risk of dust-mediated transmission of healthcare-associated infections.Materials and Methods. Dust sampling (n = 41) was carried out using sterile gloves and containers from ventilation grilles and adjacent air ducts of the exhaust ventilation systems in various healthcare settings. Size and shape of dust particles were studied by means of scanning electron microscopy and dynamic light scattering. Elemental analysis (CHNSO) was conducted employing high temperature catalytic oxidation. Bacterial composition of the dust was investigated using a VITEK 2 Compact biochemical analyzer while viral diversity was screened by polymerase chain reaction.Results. Dust in healthcare units consisted of globular particles and/or microsized fibers. Regardless of the healthcare setting, globular particles prevailed in the dust structure. Dust nanoparticles was characterised by an average first size peak of 85.6 ± 12.6 nm and an average second peak of 307.1 ± 76.2 nm. Dust collected in non-surgical units contained a higher nitrogen content than surgical settings (p < 0.001). Proportions of hydrogen, carbon, and sulfur did not differ between non-surgical and surgical units. The dust collected from healthcare settings in different cities also varied in nitrogen content (p = 0.033). A wide microbial diversity was detected in dust samples and a high frequency (46.34%) of its contamination was found. In surgical departments, dust contamination was notable for multidrug-resistant bacteria (28.57%), while viruses prevailed in non-surgical departments (23.3%).Conclusions. Dust generated in surgical departments contains nanosized particulate matter, multidrug-resistant microorganisms, and a prominent organic component all defining it as a possible reservoir of multidrug-resistant microorganisms which may potentially cause healthcare-associated infections via airborne transmission.